Effects of dung beetle activity on tropical forest plants - Andresen, Ellen; Urrea-Galeano, Lina Adonay (Frontiers in Ecology and Evolution, 2022)
Dung beetles are recognized as providers of important ecosystem functions, most of which are derived from the removal of vertebrate dung from the soil surface. These insects occur in nearly all terrestrial biomes but are most diverse in the humid tropics. Several of the ecological functions attributed to dung beetles are related to their direct and indirect interactions with plants. Among these functions, the secondary dispersal of seeds defecated by mammals has received the most attention in tropical forests. Nonetheless, while several aspects of secondary seed dispersal by dung beetles are relatively well understood, others remain understudied or have not been addressed at all. Thus, a broad generalization about the effects of secondary seed dispersal by dung beetles on plant fitness remains somewhat elusive. Furthermore, other effects of dung beetle activity on tropical plants have received very little attention. A few studies have shown that through their behaviors of dung burial and soil-excavation, dung beetles can shape seed bank structure and dynamics. Also, though numerous greenhouse studies and field experiments in agricultural lands and temperate grasslands have shown that dung beetle activity increases plant nutrient uptake and yield, it is uncertain whether such effects are common in tropical forests. Here, we review and synthesize our current knowledge on how dung beetles affect tropical forest plants by dispersing defecated seeds, shaping the structure and dynamics of seed banks, and influencing the performance of understory seedlings. We focus on the Neotropics, where most studies on the effects of dung beetles on tropical forest plants have been carried out, but we also show results from other regions and biomes, to present a more general picture of these beetle-plant interactions. Throughout the review we emphasize aspects that need more research to allow generalizations and point out those questions that remain unanswered. We hope that this review will stimulate more research about the fascinating interactions between dung beetles and plants in tropical ecosystems.